Today Your Style, Tomorrow The World: punk, fashion and visual imaginary (ModaPalavra e-periódico, 2019)
In this article we will analyze the punk movement as an innovator in fashion and contemporary visual imagery. The interpenetrations between these worlds will be approached through the trajectories of Vivienne Westwood, Malcolm McLaren and Jamie Reid. To explain these crosses, we will take a three-level approach: first, we analyze the emergence of punk in England in the mid-1970s, as well as the socio-economic context that allowed this emergence; then we will search the connection between fashion and punk, how it has been and influenced each other; finally, we will study the lasting impact of this fashion / punk link through the focus on graphic design. The perspective is to perceive the creation and perpetuation of a visual imaginary of punk up to the present considering its legacy and probably even its memory.
Keywords: fashion; visual culture; (post)punk subculture